The classroom as a space of resistance. Cooperation, gratitude and collective memory between neuroscience and social science - Mollès, Dévrig; Parada-Ulloa, Marcos (Frontiers in Sociology, 2025)
This article explores social transformation through pedagogy, historical consciousness, social science, and neuroscience. Modern educational systems perpetuate social hierarchies. The meritocratic narrative of neoliberalism is a new form of social Darwinism. Behind this illusion lie the mechanisms of accumulated history, social reproduction, and the inheritance of economic, social, cultural, and symbolic capitals. Collective memory is one of these capitals, cultivated by the elites. In contrast, the memory of the vanquished fades into oblivion. Therefore, democratic pedagogy aims to build collective memory and a historical consciousness of equality, inequality, and human rights. This project requires cognitive and methodological tools for both teachers and students. Our proposal is both theoretical and practical. Theoretically, we aim to build a historical awareness and resilience capacities to address the algorithmic colonization. Cooperative pedagogy and neuroscience bring constructive tools. This approach fosters a new rationalism and complex thinking that unifies natural, social, and human sciences into a cohesive pedagogical praxis. We propose to build collective memory and historical awareness among students, pedagogical team, and families. This involves teacher training, an emotional and prosocial climate, cooperative skills, historical research teams, collecting of family memories, and collective synthesis. The project fosters social bonds and skills for democratic sovereignty. Methodologically, the research employs a critical bibliographical review and content analysis from CAIRN, OpenEdition, ScienceDirect, Web of Science, ERICH+, EBSCO, Scopus, and Google Scholar. The selected bibliography includes authors from Canada, Chile, England, France, Germany, India, Switzerland, the Philippines, and the United States.